Pragmatic Politeness of the Imperative Speech Used by the Elementary School Language Teachers - Raihany, Afifah; Rabbianty, Eva Nikmatul (OKARA: Jurnal Bahasa dan Sastra, 2021)
As a means of communication, the politeness aspect of language always comes together with interpersonal communication. People can reflect politeness in communication activities through their verbal language. This research aims to analyze and describe the elementary school language teachers’ imperative speech focusing on the form, meaning, and imperative pragmatic politeness. This study is descriptive qualitative research. The data were teachers’ speeches during the teaching-learning process. The data were collected by using the observation method with observing, recording, and note-taking techniques. The imperative pragmatic meaning of the prohibition and interrogative speech describes the pragmatic meaning of imperative commands widely used by SD Integral Lukman al-Hakim Sumenep language teachers. Meanwhile, according to Leech’s politeness principles, the teachers use six maxims categories; tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. In addition, imperative speech with the complete agreement is also found, namely in the form of action as a student’s reaction to the teacher’s imperative speech; the findings also prove that imperative speech found in the imperative form and the non-imperative form of politeness. Both of the politeness in the speech of the Language teacher forms are based on the construction of Leech’s politeness principles.